2005
DOI: 10.1103/physrevlett.94.185502
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Dense Sodium

Abstract: High-pressure high-temperature synchrotron diffraction measurements reveal a maximum on the melting curve of Na in the bcc phase at approximately 31 GPa and 1000 K and a steep decrease in melting temperature in its fcc phase. The results extend the melting curve by an order of magnitude up to 130 GPa. Above 103 GPa, Na crystallizes in a sequence of phases with complex structures with unusually low melting temperatures, reaching 300 K at 118 GPa, and an increased melting temperature is observed with further inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
160
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(180 citation statements)
references
References 44 publications
20
160
0
Order By: Relevance
“…An example is the complexity of structure revealed at HP. Contrary to the conventional understanding that the crystal structures at HP becomes increasingly simple like arrays of closely packed balls, HP increases the interaction of the inner electrons, and atoms may become irregularly-shaped and non-spherical, resulting in very complicated crystal structures and very large unit cells [345,346] (Fig. 19).…”
Section: Hp Crystallographymentioning
confidence: 89%
“…An example is the complexity of structure revealed at HP. Contrary to the conventional understanding that the crystal structures at HP becomes increasingly simple like arrays of closely packed balls, HP increases the interaction of the inner electrons, and atoms may become irregularly-shaped and non-spherical, resulting in very complicated crystal structures and very large unit cells [345,346] (Fig. 19).…”
Section: Hp Crystallographymentioning
confidence: 89%
“…Between 2002 and 2008, a number of phase transitions of sodium at pressures up to 160 GPa were observed [42][43][44]. In 2009, in three letters to Nature in the same issue [45][46][47], it was shown that both lithium and sodium lose their metallic character under pressure.…”
Section: From Solvated Electrons To Electridesmentioning
confidence: 99%
“…
Recent experiments have shown that sodium, a prototype simple metal at ambient conditions, exhibits unexpected complexity under high pressure [1][2][3][4] . One of the most puzzling phenomena in the behaviour of dense sodium is the pressureinduced drop in its melting temperature, which extends from 1000 K at ∼30 GPa to as low as room temperature at ∼120 GPa 1 .
…”
mentioning
confidence: 99%